Derrida After the End of Writing Political Theology and New Materialism - Crockett, Clayton (Fordham University Press, 2017)
This book explores some of the implications of interpreting Derrida through the new materialist lens of technicity or plasticity, attending to the significance of ethics, religion and politics in his later work. Here the intersection of religion and politics becomes the site for Derrida to develop a "political theology without sovereignty." By reading Derrida from a new materialist perspective, fresh readings are offered of his ideas of sovereignty, religion, responsibility, and mourning, including engagements with Malabou, Timothy Morton, John D. Caputo, and Karen Barad...Derrida's philosophy is relevant not just for human ethical language and animality, but to profound developments in the physical and natural sciences, as well as ecology. Here is a new reading of Derrida beyond the conventional understandings of poststructuralism and deconstruction, that is responsive to and critical of some of the newer trends in Continental philosophy.
Description based on print version record.
KU Select 2017: Front list Collection
Keywords: Philosophy / Political; Political Science / Political Ideologies; Political science; Electronic books